2013
DOI: 10.1371/journal.pone.0059833
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and the Colonization Route of One of the Oldest North American Invasive Insects: Stories from the Worn Road of the Hessian Fly, Mayetiola destructor (Say)

Abstract: An integral part to understanding the biology of an invasive species is determining its origin, particularly in pest species. As one of the oldest known invasive species, the goals of this study were to evaluate the evidence of a westward expansion of Hessian fly into North America, from a potential singular introduction event, and the population genetic structure of current populations. Levels of genetic diversity and population structure in the Hessian fly were compared across North America, Europe, North Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…In the current study, SSGP transcript abundance in the six field collections fell into three geographical groups based on similarity of SSGP expression and wheat class grown in the geographical region: (1) southeastern USA; (2) central USA; and (3) the Middle East. These groupings were also in agreement with a previously published population survey that revealed the worldwide structure of Hessian fly populations using microsatellite markers (Morton & Schemerhorn, 2013 ). Alabama and Georgia are located in the southeastern USA, where soft-red-winter wheat varieties are grown, and multiple R genes ( H 3, H 5, H 6, H 7 H 8, H 9 and H 13) have been deployed in adapted wheat varieties (Cambron et al ., 2010 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, SSGP transcript abundance in the six field collections fell into three geographical groups based on similarity of SSGP expression and wheat class grown in the geographical region: (1) southeastern USA; (2) central USA; and (3) the Middle East. These groupings were also in agreement with a previously published population survey that revealed the worldwide structure of Hessian fly populations using microsatellite markers (Morton & Schemerhorn, 2013 ). Alabama and Georgia are located in the southeastern USA, where soft-red-winter wheat varieties are grown, and multiple R genes ( H 3, H 5, H 6, H 7 H 8, H 9 and H 13) have been deployed in adapted wheat varieties (Cambron et al ., 2010 ).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the variations in expression documented are not because of different wheat genotypes. Therefore, the documented variation in expression of SSGP genes is associated with genetic adaptations that accumulated over time from environmental and agro-ecosystem selection pressures (Morton et al ., 2011 ; Morton & Schemerhorn, 2013 ). These selection pressures could influence population structure and evolution in the field and influence the expression of effectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microsatellite data [ 15 ] and virulence assays [ 13 ] indicated that there is just one major population of HF in the SE US with population structure as well as microscale diversity [ 13 , 15 ]. HF populations from Holmes County, Mississippi, and Florence County, South Carolina, had a different population identity when compared to populations from other counties from SE states [ 16 ]. The H12 , H13 , H18 , H24 – H26 , H31 – H33 , and Hdic genes are still effective in multiple SE counties, but H24 – H26 can be associated with undesirable agronomic traits [ 14 ].…”
Section: Introductionmentioning
confidence: 99%